2006
DOI: 10.1021/ja0613714
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Signaling Molecule c-di-GMP

Abstract: Using UV, CD, and NMR, we demonstrate that the important bacterial signaling molecule involved in biofilm formation, cyclic diguanosine monophosphate (c-di-GMP), exists as a mixture of five different but related structures in an equilibrium that is sensitive both to its concentration and to the metal present. At the lower concentrations used for UV and CD work (0.05 -0.5 mM) Li + , Na + , Cs + , and Mg 2+ favor a bimolecular self-intercalated structure, while K + , Rb + , and NH 4 + favor formation of one or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(133 citation statements)
references
References 53 publications
9
123
0
1
Order By: Relevance
“…This may be related to the varying degree of dimerization of c-di-GMP in solution (20). Because this effect is limited to the first few injections and does not interfere with the sigmoidal part of the binding curve, we have eliminated the first three data points from the fit (Fig.…”
Section: Activation Of the Pled Diguanylate Cyclase Does Not Interfermentioning
confidence: 99%
“…This may be related to the varying degree of dimerization of c-di-GMP in solution (20). Because this effect is limited to the first few injections and does not interfere with the sigmoidal part of the binding curve, we have eliminated the first three data points from the fit (Fig.…”
Section: Activation Of the Pled Diguanylate Cyclase Does Not Interfermentioning
confidence: 99%
“…There is, however, no strict correlation; for example, in P. aeruginosa PA14, a mutation of the gene encoding the GGEEF protein PA3343, which is active in cyclic di-GMP synthesis, leads to hyperbiofilm formation, whereas the overexpression of PA2870 and PA3343, which both lead to increases in the cellular level of cyclic di-GMP, has no effect on biofilm formation in the wild type (35). An added complexity is that the nucleotide adopts different but related structures with different counterions and under different concentrations (65). A bimolecular intercalated structure found at low concentrations with Na ϩ and Mg 2ϩ is also the form in which cyclic di-GMP binds to PleD and may be the active form for signaling.…”
Section: The Cellular Organization Of Cyclic Di-gmp Signaling Systemsmentioning
confidence: 99%
“…BcsA's C-terminal PilZ domain binds an intercalated c-di-GMP dimer (Zhang et al, 2006) (Fig. 24 and Fig.…”
Section: Bcsa Binds a C-di-gmp Dimer On The β-Barrel Surfacementioning
confidence: 99%
“…C-di-GMP monomers and dimers (Zhang et al, 2006;Gentner et al, 2012) are both recognized by effector proteins via PilZ domains, first identified as regulatory components of cell motility (Christen et al, 2007), which comprise an "RxxxR" motif in a flexible linker region followed by a β-sheet or β-barrel that contains a "DxSxxG" motif (Amikam and Galperin, 2006). Both sequence motifs have been shown to interact with cdi-GMP in structures of isolated PilZ domains (Benach et al, 2007;Ko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation